Deep Learning Technique of Sentiment Analysis for Twitter Database - Gattan, Atif M. (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Sentiment investigation is the progression of calculating, recognizing as well as classifying the people mentality stated in the outline of the manuscript and the outlook of the individual concerning the particular subject matter can be investigated with the assist of that statistics. The information is accumulated by way of the assistance of API in favor of classifying of the end outcome based on the information collected as in Negative way, Neutral way and Positive way with the support of the scoring polarity allocated in favor of every statement that are collected. These data are fruitful for discovering and enhancing the consumer requirements and to acquire better tune-up. Major improvement of using the concept of sentiment analysis is to develop the user needs by straightforwardly collecting the information from the outsized set of consumers.